2018
DOI: 10.2196/mhealth.8478
|View full text |Cite
|
Sign up to set email alerts
|

Concussion Assessment With Smartglasses: Validation Study of Balance Measurement Toward a Lightweight, Multimodal, Field-Ready Platform

Abstract: BackgroundLightweight and portable devices that objectively measure concussion-related impairments could improve injury detection and critical decision-making in contact sports and the military, where brain injuries commonly occur but remain underreported. Current standard assessments often rely heavily on subjective methods such as symptom self-reporting. Head-mounted wearables, such as smartglasses, provide an emerging platform for consideration that could deliver the range of assessments necessary to develo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…Smartglasses, such as for example Google Glass, contain a complex array of sensors, and are able to collect video and audio data from the user and the environment. They are also able to monitor movement and velocity through an inbuilt gyroscope and accelerometer [35]. Smartglasses can provide users with video and audio guidance through an inbuilt display and bone conduction/audio speakers.…”
Section: Smartglasses In Classesmentioning
confidence: 99%
“…Smartglasses, such as for example Google Glass, contain a complex array of sensors, and are able to collect video and audio data from the user and the environment. They are also able to monitor movement and velocity through an inbuilt gyroscope and accelerometer [35]. Smartglasses can provide users with video and audio guidance through an inbuilt display and bone conduction/audio speakers.…”
Section: Smartglasses In Classesmentioning
confidence: 99%
“…Six studies investigated the convergence validity of inertial sensor-based PC assessments [12,13,16,[40][41][42]. Two studies were excluded from the validity synthesis as they investigated the convergence validity by comparing the measure to a second inertial sensor measurement [40,41], thus not comparing the method of measurement to another accepted standard.…”
Section: Convergence Validitymentioning
confidence: 99%
“…Six studies investigated the convergence validity of inertial sensor-based PC assessments [12,13,16,[40][41][42]. Two studies were excluded from the validity synthesis as they investigated the convergence validity by comparing the measure to a second inertial sensor measurement [40,41], thus not comparing the method of measurement to another accepted standard. The four remaining studies used a clinical standard comparator (ie BESS/mBESS errors) and reported varying correlation coefficients ranging from r = 0.01 to -0.77, rho = 0.16 to 0.94 and ICC = 0.68 to 0.94 [12,13,16,42].…”
Section: Convergence Validitymentioning
confidence: 99%
See 2 more Smart Citations